2019
DOI: 10.20945/2359-3997000000159
|View full text |Cite
|
Sign up to set email alerts
|

Brazilian multicenter study on pegvisomant treatment in acromegaly

Abstract: Objective: Investigate the therapeutic response of acromegaly patients to pegvisomant (PEGV) in a real-life, Brazilian multicenter study. Subjects and methods: Characteristics of acromegaly patients treated with PEGV were reviewed at diagnosis, just before and during treatment. All patients with at least two IGF-I measurements on PEGV were included. Efficacy was defined as any normal IGF-I measurement during treatment. Safety data were reviewed. Predictors of response were determined by comparing controlled ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 32 publications
2
15
0
2
Order By: Relevance
“…In the phase III study, injection site reactions were reported in six patients (5%) receiving pegvisomant [11]. In the Brazilian real-life study, it was reported in 4.6% of patients [14]. Pain from injection was reported in 2.7% patients.…”
Section: Cutaneous Lipohypertrophymentioning
confidence: 98%
See 3 more Smart Citations
“…In the phase III study, injection site reactions were reported in six patients (5%) receiving pegvisomant [11]. In the Brazilian real-life study, it was reported in 4.6% of patients [14]. Pain from injection was reported in 2.7% patients.…”
Section: Cutaneous Lipohypertrophymentioning
confidence: 98%
“…In the phase III study, one patient with 15 mg/day of pegvisomant withdrew due to persistent headaches [11]. In the Brazilian real-life study, headaches were reported in two cases (1.8%) [14].…”
Section: Headachementioning
confidence: 99%
See 2 more Smart Citations
“…T wo studies published in this present issue of the Archives of Endocrinology and Metabolism, by Natalia Garcia Basavilbaso (1) and coworkers, as well as the one by Cesar Boguszewski and coworkers (2), describe the treatment response in real-life of pegvisomant (PEGV) therapy in acromegaly patients, including aspects of safety and efficacy.…”
mentioning
confidence: 99%